2022
DOI: 10.3390/app12020626
|View full text |Cite
|
Sign up to set email alerts
|

Peak Shift of Coherent Edge Radiation Spectrum Depending on Radio Frequency Field Phase of Accelerator

Abstract: Spectra of coherent edge radiation (CER) were observed at the S-band linac facility of Kyoto University Free Electron Laser. A local maximum was observed in the CER spectrum on-crest operation of the radio frequency (RF) field. As the phase of the RF field was shifted from the crest, the frequency of the maximum decreased, and the CER spectrum approached a spectrum of Gaussian-distributed electrons in a bunch. It was found that this strange spectrum can be explained by a model in which a satellite pulse exists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Figures 2(c) and (d) show the frequency dependence of ratios of the CER power P on /P off , where P on is the CER power with the FEL at ΔL = +2 μm and P off is the CER power without the FEL at ΔL = +23 μm. It has been confirmed that the electron distribution in a bunch can be well approximated by a Gaussian when the FEL is not oscillating [23,25]. In the frequency region of 0.3 − 1.0 THz, where the CER power was strong sufficiently, it is noted that the CER power ratios had the following relationship [26]:…”
Section: Cer Spectra On Perfectly Synchronized Optical Cavity Lengthmentioning
confidence: 83%
See 2 more Smart Citations
“…Figures 2(c) and (d) show the frequency dependence of ratios of the CER power P on /P off , where P on is the CER power with the FEL at ΔL = +2 μm and P off is the CER power without the FEL at ΔL = +23 μm. It has been confirmed that the electron distribution in a bunch can be well approximated by a Gaussian when the FEL is not oscillating [23,25]. In the frequency region of 0.3 − 1.0 THz, where the CER power was strong sufficiently, it is noted that the CER power ratios had the following relationship [26]:…”
Section: Cer Spectra On Perfectly Synchronized Optical Cavity Lengthmentioning
confidence: 83%
“…Figures 2(a) and (b) show the measured CER spectra at the detuning length of the optical cavity (ΔL) of +2 μm (where the CER power was minimum) and +23 μm. Because the spectra were measured in the atmosphere, absorption because of water vapor was observed at the frequencies of 0.56, 0.75, 0.99, 1.1-1.3, 1.4, and 1.6 THz [25]. The CER spectra rapidly decreased below 0.3 THz owing to a diffraction loss of the optical system for the CER beam.…”
Section: Cer Spectra On Perfectly Synchronized Optical Cavity Lengthmentioning
confidence: 99%
See 1 more Smart Citation